Análise das mudanças na linha costeira e do turismo náutico em um recife costeiro urbano no Nordeste do Brasil - Souza, Maria Cecilia Silva (2023)
In Brazil, the reefs are distributed over approximately 3,000 km between latitudes 0º50' S to 18º00' S. According to Massei et al. (2023), coastal reefs in the Northeast region of Brazil are located parallel to the coastline, at depths of 5 to 10 m, and the majority develop on the beach rocks, as is the case of the Seixas reef . This study aims to analyze the growth of tourism, geoecological diversity in the Seixas reef and changes in the coastline in the municipality of João Pessoa. The main methodologies were guided and characterized as multidisciplinary as they dealt with data relating to environmental geomorphology, species biology, environmental management, coastal and marine tourism, resulting in the compilation of these over the years resulting in an analysis of the dynamics of change of the coastline on the face of Seixas beach between the years 2010 and 2020: in which it was evidenced that the dynamics of the coastline over a period of 10 years, identified a predominance of critical erosion for the two satellites Landsat and Sentinel- 2, making it possible to observe intense dynamic activity in the region. In addition to highlighting the recent evolution of tourism (distribution of vessels over reef environments and growth of the service sector (accommodation) in the coastal area) between the years 2010 and 2020; in the last 10 years reveals a significant increase in use in the Seixas reef environment. When analyzing this data spatially, we observed that tourism showed a pattern of expansion from North to South. Vessels departing from the Tambaú Seixas route are the majority on the reef, currently representing around 50% of vessels. It is recommended that more specific studies be carried out, but it has been proven that the dynamics of the coastline in the area is influenced by the reef environment and this is conditioned by conservation factors that unregulated tourism does not seem to respect, therefore, this activity increasingly out of control, it reached the point where the environment did not have enough resilience to continue protecting the coast.